ANALISIS KELAYAKAN INVESTASI MENGGUNAKAN METODA DISCOUNTED CASH FLOW TAMBANG GALENA PT. TRIPLE EIGHT ENERGY, KECAMATAN KOTO PARIK GADANG DIATEH KABUPATEN SOLOK SELATAN PROVINSI SUMATERA BARAT - Dirga Sidauruk; Muhammad Giatman; Murad Murad (Journals Mining Engineering : Bina Tambang, 2018)
To perform the feasibility analysis of investment can be done by using severalmethods, PT. Triple Eight Energy with galena commodity using discounted cash flowas its method of analysis. Based on the calculation, obtained cash out flow of Rp649.289.950.100, cash in flow of Rp 2.361.317.978.504, NPV of Rp 789.154.337.450,payback period for 2 years 7,4 months, discounted payback period for 2 years 3, 5months, IRR of 30.98%, PI of 23.6300447. From these calculations it can beconcluded that, galena mine PT. Triple Eight Energy is economically viableKata kunci: analisis investasi, tambang galena, discounted cash flow